Determinants Of Enterprise Risk Management Disclosure - Dedi Putra SE,.M.S.Ak; Pebrina Swissia; Anik Irawati (Prosiding International conference on Information Technology and Business (ICITB), 2022)
This study aims to prove empirically the factors that influence the disclosure of Enterprise Risk Management (ERM). This type of research is a quantitative research. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange. The sample in this study amounted to 120 companies. The sampling method in this study was purposive sampling technique. This study uses secondary data in the form of annual reports totaling 120 samples of financial companies listed on the Indonesia Stock Exchange (IDX) in the 2017-2019 period. The analysis in this study uses multiple linear regression with the SPSS program. The results of this study indicate that the size of the company has a positive effect on the disclosure of Enterprise Risk Management (ERM). Keywords: Company size, Risk Management Committee (RMC), auditor reputation, ownership concentration, and Chief Risk Officer (CRO), Enterprise Risk Management (ERM) disclosure.